Recognition and Treatment of Tardive Dyskinesia in Individuals with Intellectual Disability - Morton, Robert O.; Morton, Lucas C.; Fedora, Rissa (Case Reports in Psychiatry, 2020)
Individuals with intellectual disability (ID) commonly suffer from comorbid psychiatric and behavioral disorders that are frequently treated by antipsychotic medications. All individuals exposed to first- and second/third- generation antipsychotics are at risk for developing tardive dyskinesia (TD), characterized by abnormal, involuntary movements of the mouth/tongue/jaw, trunk, and extremities. TD can be highly disruptive for affected individuals and their caregivers, causing embarrassment, isolation, behavioral disturbances, and reduced functioning and quality of life. Information on TD incidence in individuals with ID is limited, but 2 small US studies reported TD prevalence rates of 42-45% in inpatients with ID. The safety and efficacy of vesicular monoamine transporter type 2 (VMAT2) inhibitors approved for treatment of TD in adults have been demonstrated in multiple clinical trials, but they excluded individuals with ID. Clinical characteristics and treatment outcomes of 5 adults (aged 28–63 years) with mild-to-severe ID and TD are presented, illustrating TD symptoms before/after treatment. All individuals had multiple comorbid psychiatric, behavioral, and other medical conditions, history of antipsychotic exposure, and abnormal movements affecting the tongue/mouth/jaw (n=5), upper extremities (n=5), lower extremities (n=3), and trunk (n=2), resulting in diminished ability to speak (n=2), ambulate (n=3), and perform activities of daily living (n=3). Treatment with valbenazine resulted in meaningful improvements in TD symptoms and improved daily functioning, demeanor, and social/caregiver interactions. Given the high likelihood of antipsychotic exposure in the ID population, it is appropriate to screen for TD at every clinical visit through careful monitoring for abnormal movements and questioning the individual/caregiver regarding abnormal movements or TD-related functional impairments (i.e., speaking, swallowing, eating, ambulating, and social functioning). In this study, 5 individuals with ID and TD received once-daily valbenazine and experienced marked improvement in TD symptoms and daily functioning, resulting in increased quality of life for affected individuals and caregivers.